Case report: Primary giant osteosarcoma of the heart protruding into the pericardial space in a young woman: a case of multimodal imaging - Zhao, Ling; Li, Fei; Xu, Wenzhe; Zhao, Zhennian; Huo, Xiaoguang; Zhang, Yongting (Frontiers in Oncology, 2025)
BackgroundPrimary cardiac malignancies are rare, and primary cardiac osteosarcoma is even rarer. The prognosis is poor. Four multimodality imaging data of the same case have not been retrieved yet.CaseWe report a 21-year-old woman with osteosarcoma in the left atrium, atrial wall, and pericardial cavity. She was hospitalized for cholecystitis and chest tightness. Transthoracic echocardiogram (mixed echogenic tumor in the left atrium and pericardium), computed tomography (CT), cardiac magnetic resonance imaging (MRI) enhancement scan (heterogeneous enhancement of tumor), and positron emission tomography (PET)-CT examination (high FDG uptake of tumor) revealed mass in the left atrium, atrial wall, and pericardial cavity. According to the comprehensive analysis of multimodality imaging examination results, it was considered as a cardiac malignant tumor. A surgical plan was immediately formulated and surgical treatment was performed. The patient developed renal failure after operation. After active hemofiltration, anti-infection, anticoagulation, expectorant, cardiotonic, diuretic, nutritional support, and other symptomatic treatments, her condition was improved, and she was discharged after continuous treatment. After nine cycles of chemotherapy, the patient has been followed up for 11 months. The patient is in good condition and no recurrence has been observed.ConclusionPrimary cardiac osteosarcoma is extremely rare. Multimodality imaging, including echocardiography, CT, MRI, and PET-CT, has a high diagnostic value for cardiac osteosarcoma, which can provide reference for the feasibility and safety of surgical operation.